(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Cognitive dysfunction after COVID-19 are hypoxia, microvascular injury, immunological dysregulation, chronic inflammation, patients with mild infections also report cognitive symptoms. A recognized symptom of long COVID is “Brain Fog”, characterized by fatigue, lack of ability to concentrate and can severely affect memory and cognition. Long-term side effects of COVID-19 is Brain fog which occurs irrespective of the severity of the infection. The Medhya Dravyas (Nootropic drugs) are beneficial to improve the power of retention, grasping, discrimination and recollection thus improving the Medha (Cognition). Present clinical study is an attempt to evaluate the nootropic effect of certain drugs in Brain Fog with special reference to Covid 19. Aim: To review medicinal plants showing Medhya Karma (Nootropic activity) on signs and symptoms correlated with brain fog in Covid 19 with Ayurveda as a natural and safe remedy. Material and Methods: Materials related to Covid 19, Brain fog, Neurological symptoms cognitive impairment, Medhya Dravyas (Nootropic drugs) have been collected from different journals, Ayurveda and Modern text, Authentic websites (PubMed, Google scholar, Scopus, etc.), Observation and Results: Plants reviewed showed nootropic action by Antioxidant, Acetylcholine esterase inhibition, NMDA antagonism, Dopaminergic, Anti-amyloidogenic, Inhibition of Tau aggregation and Neuroprotection. These properties helps in the management of cognitive impairment. Conclusion-Medhya Dravyas possess nootropic and rejuvenative properties. Plants shown maximum inhibitory activities against the factors causing brain Fog by Neuroprotection and memory enhancement. It reveals the strength of the Ayurveda system as well as potential in developing new drug for memory enhancement